Preliminary Investigation On The Perforated Panel Mobility Using Finite Element Method - Putra, Azma; Rivai, Ahmad; Mun, Wai C.; Muhammad, Noryani (Trans Tech Publications, 2014)
Introduction of holes into plat-like structures is commonly found as one of practical noise control measures to reduce sound radiation. However, perforation into the panel also reduces the panel stiffness and hence increases its vibration. Since the discussion and also the analytical model to quantify this effect are lacking, this paper discusses the dynamics of a perforated panel from the results obtained using Finite Element Method (FEM). Different hole geometries are simulated to investigate their effect on the plate mobility. It is found that increasing the perforation ratio increases the plate mobility particularly at off-resonance peaks. The effect of hole size and number are also discussed in this report.